2006
DOI: 10.2471/blt.05.025718
|View full text |Cite
|
Sign up to set email alerts
|

Community surveys and risk factor analysis of human alveolar and cystic echinococcosis in Ningxia Hui Autonomous Region, China

Abstract: Objective To determine the true community prevalence of human cystic (CE) and alveolar (AE) echinococcosis (hydatid disease) in a highly endemic region in Ningxia Hui, China, by detecting asymptomatic cases. Methods Using hospital records and "AE-risk" landscape patterns we selected study communities predicted to be at risk of human echinococcosis in Guyuan, Longde and Xiji counties. We conducted community surveys of 4773 individuals from 26 villages in 2002 and 2003 using questionnaire analysis, ultrasound ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
124
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(135 citation statements)
references
References 32 publications
7
124
1
3
Order By: Relevance
“…However, the abundance and intensity of infection with E. multilocularis was comparable with that found in China. Close contact with dogs is an obvious risk factor for human CE and has been reported as a risk factor for human AE (Yang et al, 2006). To what extent these dogs pose a risk to the local human inhabitants is presently unknown, but very high human prevalences in China have been reported in areas where the local dog population has had similar levels of infection to the present report (Budke et al, 2004).…”
Section: Discussionsupporting
confidence: 49%
“…However, the abundance and intensity of infection with E. multilocularis was comparable with that found in China. Close contact with dogs is an obvious risk factor for human CE and has been reported as a risk factor for human AE (Yang et al, 2006). To what extent these dogs pose a risk to the local human inhabitants is presently unknown, but very high human prevalences in China have been reported in areas where the local dog population has had similar levels of infection to the present report (Budke et al, 2004).…”
Section: Discussionsupporting
confidence: 49%
“…La tenencia de perros fue muy común en el grupo encuestado, siendo especialmente alta en zonas rurales. Esta conducta es considerada un factor de riesgo, ya que incrementa las posibilidades de padecer hidatidosis y a mayor número de perros por hogar, mayor es el riesgo de enfermar [29][30][31] . Cifras similares a las encontradas en este estudio se describen por otros autores, tanto en sectores urbanos y rurales como en la Provincia del Limarí 28 .…”
Section: Discussionunclassified
“…Hydatidosis is rarely reported in the native European population, as most cases involve immigrants from countries where the disease is endemic; cases of disease localized within the inter atrial septum are exceptional [3][4][5][6][7][12][13][14] . Studies have reported many differences in parasite characteristics among geographic strains due to local patterns of transmission.…”
Section: Discussionmentioning
confidence: 99%
“…The disease is encountered in most parts of the world and occurs most commonly in sheep farming and cattle farming areas of South America, New Zealand, the Philippines, China, Arabia, Eastern Europe and the Mediterranean basin [3][4][5][6][7] . The parasite is a small Taenia (less than 1 cm long).…”
Section: Introductionmentioning
confidence: 99%